Android hacker's handbook - Drake, Joshua J
Includes bibliographical references and index; Looking at the ecosystem -- Android security design and architecture -- Rooting your device -- Reviewing application security -- Understanding Android's attack surface -- Finding vulnerabilities with fuzz testing -- Debugging and analyzing vulnerabilities -- Exploiting user space software -- Return oriented programming -- Hacking and attacking the kernel -- Attacking the radio interface layer -- Exploit mitigations -- Hardware attacks